2019
DOI: 10.1128/jvi.02028-18
|View full text |Cite
|
Sign up to set email alerts
|

Host Range and Population Survey of Spodoptera frugiperda Rhabdovirus

Abstract: The Sf9 and Sf21 cell lines derived from ovarian tissues of the wide-host-range phytophagous lepidopteranSpodoptera frugiperdaare widely used for research and commercial-scale production of recombinant proteins. These cell lines are chronically infected with a rhabdovirus (Sf-RV) that does not cause any overt cytopathic effects. We demonstrate that wild populations ofS. frugiperdain the eastern United States and Caribbean are infected with genetically diverse strains of Sf-RV and that this virus is also capabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Furthermore, an analysis of a dataset of deep-sequenced small RNAs bound to Ago2 in BmN cells [35] revealed abundant 20 nt reads mapping to the genome of SfRV in both polarities [58]. Since the BmN cell line, another lepidopteran cell line used for baculovirus expression, has also been reported to be persistently infected with SfRV [59], the presence of siRNA reads corresponding to the SfRV genome also suggests that SfRV RNA is targeted by endogenous Dicer-2 in this cell line. These observations provide indirect support to the hypothesis that SfRV RNA is targeted by Dicer-2 in Sf9 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an analysis of a dataset of deep-sequenced small RNAs bound to Ago2 in BmN cells [35] revealed abundant 20 nt reads mapping to the genome of SfRV in both polarities [58]. Since the BmN cell line, another lepidopteran cell line used for baculovirus expression, has also been reported to be persistently infected with SfRV [59], the presence of siRNA reads corresponding to the SfRV genome also suggests that SfRV RNA is targeted by endogenous Dicer-2 in this cell line. These observations provide indirect support to the hypothesis that SfRV RNA is targeted by Dicer-2 in Sf9 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms are loss of appetite, lethargy, body sagging, softening of the integument, and a tendency to turn off color. Some viruses studied against S. frugiperda are Rhabdovirus (Sf-RV) [61]; granulovirus (SfGV ARG) type 1, 2, and 3 [62,63]; ascovirus (SfAV-1a) [64]; ichnovirus (HdIV) [65]; and the most studied, nucleopolyhedrovirus (SfMNPV) [55,66]. Undoubtedly, this strategy has shown high efficiency in the control of S. frugiperda in in vitro evaluations.…”
Section: Biological Controlmentioning
confidence: 99%
“…Sf-rhabdovirus was found permanently infecting Sf9 cells and the virus sequence was also detected in a parental Sf cell line, Sf21 [53]. In addition, Sfrhabdovirus is infectious to the High Five cell line from the noctuid Trichoplusia ni and the SL2 cell line from D. melanogaster but is not infectious to human cell lines [53,84]. Subsequently, two lepidopteran-associated new sigma-like viruses were discovered from RNAseq data [85].…”
Section: Rhabdovirusesmentioning
confidence: 99%
“…Subsequently, two lepidopteran-associated new sigma-like viruses were discovered from RNAseq data [85]. More recently, the presence of genetically diverse isolates of Sf-rhabdoviruses was identified in naturally occurring adult S. frugiperda populations [84]. Nonetheless, no study has so far demonstrated the presence of the rhabdoviruses in any of the larval stages of FAW.…”
Section: Rhabdovirusesmentioning
confidence: 99%